Antecedents of Attitudes Towards Risky Career Choices - Verena Jung; Sascha L. Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
We explore the attitude towards risky career choices of young people in highly competitive environments. We empirically test which factors influence young elite athletes' tendency towards choosing a high-risk career option over a lower risk one; looking at the attitudes, of close to 1000 soccer players in the German "Bundesliga" professional clubs' Youth Academies, towards making real-life decisions. Generally, they face the decision early on as to whether or not they should risk quitting school to solely focus on a professional soccer career. Our study confirms that elements of expected utility, assessment of the likelihood of achievement of the aspired career as well as the potential benefit derived from this decision, explain risk-taking in competitive environments. The longer an individual survives the continuous selection process in the competitive environment, the more he thinks that he will eventually succeed - despite the increasing opportunity costs of quitting a low-risk alternative career. Initial success in the selection processes is a key trigger for the tendency to choose a career in winner-take-all markets.
Keywords: J24; J15; D81; D83; D84; L83; 330; Career choices; Risk attitude; Risk perception; Professional athletes; Young athletes; Opportunity cost; integration